2017
DOI: 10.1093/mnras/stx3123
|View full text |Cite
|
Sign up to set email alerts
|

Quasar 2175 Å dust absorbers – II. Correlation analysis and relationship with other absorption line systems

Abstract: We present the cold neutral content (H i and C i gas) of 13 quasar 2175Å dust absorbers (2DAs) at z = 1.6 -2.5 to investigate the correlation between the presence of the UV extinction bump with other physical characteristics. These 2DAs were initially selected from the Sloan Digital Sky Surveys I -III and followed up with the Keck-II telescope and the Multiple Mirror Telescope as detailed in our Paper I. We perform a correlation analysis between metallicity, redshift, depletion level, velocity width, and explo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(51 citation statements)
references
References 93 publications
9
42
0
Order By: Relevance
“…Due to the small sample size and relatively large error bars, the observed trends are only found to be correlated at 1 − 2σ significance. The connection of A V and A bump with C i is already well-established for quasar (Ledoux et al 2015;Ma et al 2018) and GRB (Zafar et al 2012;Heintz et al 2019) absorption systems, but here we include the additional information derived from the slope of the extinction, as inferred from R V . The observed trend between A V and W r (λ 1560) indicates that larger amounts of cold gas is found in more dusty sightlines, where the additional trend with R V also suggests that the dust grain size distribution are on average larger in these sightlines as well.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the small sample size and relatively large error bars, the observed trends are only found to be correlated at 1 − 2σ significance. The connection of A V and A bump with C i is already well-established for quasar (Ledoux et al 2015;Ma et al 2018) and GRB (Zafar et al 2012;Heintz et al 2019) absorption systems, but here we include the additional information derived from the slope of the extinction, as inferred from R V . The observed trend between A V and W r (λ 1560) indicates that larger amounts of cold gas is found in more dusty sightlines, where the additional trend with R V also suggests that the dust grain size distribution are on average larger in these sightlines as well.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a sample of quasar absorbers selected solely on the basis of the 2175 Å dust extinction feature, Ma et al (2018) found that all such systems are associated with strong absorption features from C i. However, only ≈ 30% of C i-selected absorbers show the characteristic dust bump at a detectable level (Ledoux et al 2015).…”
Section: The Origin Of the 2175 å Dust Extinction Featurementioning
confidence: 99%
See 1 more Smart Citation
“…The EWs of main absorption features are listed in Table 7. The neutral carbon detection is particularly interesting, since the appearance of a 2175Å extinction bump at z ∼ 2 has been linked to the presence of C i (e.g., Elíasdóttir et al 2009;Ledoux et al 2015;Ma et al 2018). We Figure 9.…”
Section: Dust-to-gas Ratiomentioning
confidence: 97%
“…The amount of C i has been observed to be correlated with the visual extinction, A V , in the line of sight to quasar and GRB absorbers (Ledoux et al 2015;Ma et al 2018;Heintz et al 2019a), suggesting a common origin for the main extinction-derived dust component and C i (see also Heintz et al 2019b). In Fig.…”
Section: The Connection Between Dust and Molecular Gasmentioning
confidence: 98%